Damage softening model and behavior of reinforced soil interface based on the Weibull distribution - Guo, Yihui; Li, Mingbao; Zheng, Junjie; Yao, Wenjie (Frontiers in Built Environment, 2023)
Based on the trilinear model of the reinforced soil pullout interface, aiming at the softening phenomenon of the geogrid reinforced soil interface during the pullout process, considering the damage softening of the reinforced soil interface during the pullout process, the damage softening model of the reinforced soil interface is proposed. The damage variable factor D is introduced, and it is assumed that D is a function of the interface displacement. The two-parameter Weibull distribution function is used to express the damage evolution law of the reinforced soil interface. Based on the basic control equation of the reinforced soil interface, the calculation model of the stress state of the geogrid at different stages under the pull-out load is deduced. In order to verify the accuracy and applicability of the model, the prediction results of the model are compared with the test results and the ideal elastic-plastic model, hyperbolic model, elastic exponential softening model and the damage softening model based on Lognormal distribution function proposed in this paper. The distribution of interfacial shear stress is studied, and the influence of parameters at each stage is analyzed. The results show that in the elastic stage, with the increase of shear stiffness, the maximum shear stress at the interface increases, and the curvature of the curve also increases, while the elastic modulus is the opposite. In the softening stage, with the increase of softening length, the peak value of the curve moves to the free end. In the residual stage, the shear stress increases from the drawing end to the free end and tends to the residual stress. The research results accord with the actual situation and can be applied to reinforced soil engineering.